Shock Wave and Singular Solitary Wave Perturbation with Gardners Equation Having Dispersion Triplet (Contemporary Mathematics, 2025)
The current paper recovers the shock wave and solitary wave solutions to the well-known Korteweg-de Vriesmodified Korteweg-de Vries (KdV-mKdV) equation with perturbation terms that is alternately known as the Gardners equation. The integration scheme adopted in this work to retrieve such solutions is the G′/G-expansion. The results appear with parameter constraints for the existence of such waves and these are also presented.
Keywords: shock wave, solitary wave, Gardners equation